Prophylactic antibiotics for hysterectomy and cesarean section: amoxicillin-clavulanic acid versus cefazolin - Malik, Jyoti; Das, Sibadatta; Das, Ashima; Rai, Pinki (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: To compare amoxicillin-clavulanic acid with cefazolin as short term antibiotic prophylaxis in women undergoing hysterectomy and elective casarean section. Methods: 60 women undergoing hysterectomy were randomly assigned either to 2.4 g intravenous amoxicillin-clavulanic acid (AMX/CL) or 2 g cefazolin 30 min before hysterectomy. 122 women delivered by elective cesarean were randomized to a single dose of either of above antibiotics at cord clamping. Each patient was assessed daily until discharge for evidence of febrile status and the presence of infection at the operative site and urinary tract. Results: Infectious morbidity was found in 11% and 12.5% of hysterectomy patients in AMX/CL and cefazolin cases respectively. 10 women had post-cesarean infections (6 AMX/CL, 4 cefazolin, p=0.51). Conclusions: Broad spectrum amoxicillin-clavulanic acid was not superior to cefazolin in prevention of post-operative infection when given as prophylaxis in hysterectomy and elective cesarean section.